Minimally displaced tibial tuberosity avulsion fracture in nine skeletally immature large breed dogs - von Pfeil, D. J. F.; DeCamp, C. E.; Ritter, M.; Probst, C. W.; Dejardin, L. M.; Priddy, N., II; Hayashi, K.; Johnston, S. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
Objective: The objective of this study was to describe the clinical and radiographic features, as well as the treatment and outcome of minimally displaced tibial-tuberosity-avulsion-fractures (MDTTAF).Materials and methods: Signalment, history, diagnostics, therapy, and outcome were recorded. Follow-up was documented as re-examination, radiographic assessment or telephone conversation.Results: Nine large breed dogs that were presented with lameness originating from the proximal tibia were included. All showed signs of pain when pressure was applied to the tibial tuberosity. There was no stifle instability or intra-articular disease. The main feature on mediolateral radiographs was a widened tibial-tuberosity-physis with reactive new bone and loss of edge definition of the epiphyseal and metaphyseal margins. Non-surgical treatment was chosen in eight dogs, and surgery in one dog. Radiographic follow-up showed progressive closure of the tibial-tuberosity-physis and healing. Clinical signs resolved at a median of 28 days (range: 14–120).Discussion: Minimally displaced tibial-tuberosity-avulsion-fractures should be a differential diagnosis in skeletally immature large breed dogs older than nine months of age with signs of subtle pelvic-limb lameness, and signs of proximal tibial pain, but no evidence of stifle joint disease. Thorough clinical examination and critical review of bilateral radiographs are important to diagnose MDTTAF. The outcome in these cases suggests that the prognosis for MDTTAF is excellent. Age and size of the affected dogs in this study differ from an earlier publication that illustrated more severely displaced tibial tuberosity avulsion fractures, occurring mainly in terriers around five months of age.
Keywords: Tibial tuberosity avulsion fracture; dog; stifle; pelvic-limb-lameness